IDENTIFIKASI KESULITAN PELAKSANAAN PENGAJARAN SEPAKTAKRAW DI SLTP NEGERIKOTA YOGYAKARTA - M. Husni Thamrin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
This research was extended of the previous research in all Senior High School, YogyakartaProvince (1996). This research seeks to identify the obstacles teaching of sepaktakraw inJunior High School Yogyakarta, also to explore the degree to which potential problem ineach factor occurs. Population used in this study based on health and physical educationteacher in all Junior High School Yogyakarta with 40 respondents. 16 State Junior HighSchool in Yogyakarta have been used for the population. Questionnaire technique insteadof survey methods is used. We use the descriptive percentage to analyze a research model.The results indicates that 3 potential problem factors on teaching of sepaktakraw in JuniorHigh School. Those factors are curriculum, teacher, and physical and facility education.Physical and facility education factor has difficulty major problems with 51, 67 % comparewith curriculum 41.25 % and teacher factor 32.5 %.Kata kunci: identifikasi, kesulitan, sepaktakraw